Resonance scattering of neutrons on the nanostructure - Takybaev, Н.Ж.; Kurmangalieva, В.О.; Zhumabekova, В.Н. (Recent Contributions to Physics, 2008)
Problem of the resonance scattering of neutrons on the nanostructure is considered within the bounds exact current task modeling problem – neutron scattering with systems of two fixed heavy nucleus. It can be atomic nucleus in monocrystals or in the nanostructure. As scattering systems considered nucleus of uranium.